Psycho-social challenges faced by caregivers of children with Cerebral palsy in Dzivarasekwa Suburb, Harare, Zimbabwe : implications for social work practice - Mukushi, Adam Tafadzwa (University of Limpopo, 2018)
Disability is most prevalent in low income countries and communities. Cerebral palsy c is one of the disabilities that is affecting a sizeable number of children in low income countries. This study sought to explore the psycho-social challenges faced by caregivers of children with cerebral palsy in Dzivarasekwa Suburb in Zimbabwe. The study had the following objectives: to identify the psycho-social challenges facing caregivers of children with cerebral palsy, to appraise individual characteristics of caregivers which predispose them to stress, social exclusion and other psychosocial challenges, to establish which coping mechanisms are employed by caregivers of children living with cerebral palsy in response to the challenges they are facing and also to suggest possible solutions/ strategies social workers may employ to improve caregiving of children with cerebral palsy. The study used a qualitative approach in exploring the psychosocial challenges caregivers face. The qualitative approach was useful as participants were able to participate freely giving a more realistic picture of their challenges. The research used an exploratory-descriptive case study design in exploring challenges faced by caregivers of children with cerebral palsy in Dzivarasekwa Suburb. Data was then collected using in-depth interviews and Focus Group Discussions. Participants were caregivers of children with cerebral palsy, a hospital psychologist as well as social workers for a local NGO supporting the rehabilitation work at a local hospital. Data were analysed used the Thematic Context Analysis method. The research concludes that caregivers are subjected to stressing conditions, lack the financial means of caring for a child with CP; caregivers employ negative strategies to the problems they face which include using the children to beg, prostitution among others. The study recommends that, government should lead initiatives for supporting children with disabilities and their families, formation of support groups for parents of children with cerebral palsy, and continuous training of frontline workers in disability to avoid burn out.
Thesis(M.A. (Social Work)) -- University of Limpopo, 2018
Keywords: Disability; Social workers; Caregivers; Cerebral palsy; Caregivers